HUBUNGAN STATUS MARITAL DENGAN TINGKAT KECEMASAN AWAK KABIN PADA PENCABUTAN PERSYARATAN HASIL TES SCREENING COVID-19 DALAM PELAKSANAAN PENERBANGAN DOMESTIK TAHUN 2022 - Fadhilah Qostholani Augisna (2023)
The COVID-19 pandemic has caused an increase in anxiety among the public, especially workers who interact with other people, such as cabin crews. The Ministry of Transportation, in order to suppress COVID-19 spreading and reduce the anxiety level of workers in the aviation sector, issued regulations for passengers traveling by airplane to attach the results of the COVID-19 screening and in early 2022, the regulation was revoked while the number of positive cases of COVID-19 keeps increasing. In addition, marital status is an aspect that affects the level of anxiety. Studies regarding the relationship between marital status and anxiety levels among cabin crews during the COVID-19 pandemic in Indonesia are lacking. This study aimed to determine the relationship between marital status and flight attendant anxiety level in the revocation of requirements for COVID-19 screening test result requirement on domestic flights in 2022. The design of this study was cross-sectional, with a sample size of 79. Marital status and anxiety levels were collected using personal data and the Hamilton Anxiety Rating Scale (HARS) questionnaire. The results showed a relationship between marital status and anxiety level (p=0.025). An increase in the anxiety level related to the marital status of cabin crews is caused by the fear of being infected with COVID-19, which will cause loneliness, especially for cabin crews with marital status not married.